Influence of the cultivation system in the aroma of the volatile compounds and total antioxidant activity of passion fruit - Janzantti, Natalia S. [UNESP]; Macoris, Mariana S. [UNESP]; Garruti, Deborah S.; Monteiro, Magali [UNESP] (Elsevier B.V., 2012)
The aim of this study was to investigate the influence of the cultivation system on the volatile composition of the passion fruit and to determine the odoriferous contribution of the compounds for the aroma of the organic and conventional fruit, besides to assess the total antioxidant activity. The volatile compounds were isolated from dynamic headspace, separated by high-resolution gas chromatography and the odoriferous contribution to the passion fruit aroma was evaluated using the OSME technique. Total antioxidant activity was determined using the ABTS radical reaction. The organic and conventional passion fruit showed similar volatile profile, although some differences occurred. Ethyl 2-propenoate, 2-methyl-1 -propanol, diethyl carbonate and ethyl hexanoate were threefold higher in the organic fruit while butyl acetate, hexanal, cis-3-hexenyl acetate and trans-3-hexenyl butanoate were threefold higher in the conventional fruit. Hexanoate and acetate esters, and saturated alcohols described as fruity, sweet, citrus and passion-fruit aroma showed the highest odorific intensity in the organic fruit. Furthermore, trans and cis-3-hexenyl acetate and alpha-copaene, alpha-terpineol, D-limonene, trans-beta-ocimene and delta-cadinene had higher contribution to the organic passion fruit aroma. on the other hand, unsaturated alcohols, beta-myrcene and beta-linalool described as grass, sulfur-like and passion-fruit aroma were higher in the conventional fruit. The organic passion fruit showed higher levels of total phenolic compounds and total antioxidant activity than the conventional fruit, suggesting that the cultivation system influenced the production of antioxidant bioactive compounds. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Volatile profile; Aroma; Olfactometry; Passion fruit; Organic system